Overcoming the Challenges of Silage Production: Insight into the Importance of Silage Additives - Firla Amalia Resmawan; Asri Peni Wulandari (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
The lack of high-quality feed remains a critical global challenge that demands that demands long¬term, sustainable solutions. Ensiling has emerged as a key strategy for preserving forage; yet significant challenges persist, particularly regarding nutrient losses and aerobic spoilage during storage. Poor silage quality not only reduces the net nutritional value of the feed but also adversely affects herd health and productivity. This review provides a comprehensive overview of recent advancements in silage technology, focusing on the pivotal role of additives in enhancing fermentation dynamics, preserving essential nutrients, and maintaining post-opening aerobic stability. The biochemical profile of the feedstock significantly dictates the specific requirement for additives, ranging from water-soluble carbohydrate sources and bacterial inoculants to chemical enzymes and organic acids. Unlike previous literature that predominantly focuses on temperate forages, this study highlights the integration of underutilized tropical biomass resources, such as cassava leaves and oil palm fronds. Furthermore, it explores novel biotechnological interventions, including microencapsulation and multi-omics technologies, which offer innovative pathways to optimize additive efficiency. By bridging conventional conservation practices with advanced molecular tools, this study highlights the potential of silage additives to provide a sustainable, resilient, and region-specific feed supply for the modern livestock sector.